Pengujian Pertumbuhan Bibit Anggur Melalui Pemberian Pupuk Menggunakan Rancangan Acak Lengkap - Dimas Arza Nugraha; M. Fajar Alif; Nova Oktavia Sitinjak; Rini Sartika; Sudianto Manullang; Putri Maulidina Fadilah (PT. Sharia Journal and Education Center, 2024)
This study aims to provide the effect of various types of fertilizer on the growth of grape seedlings using a Completely Randomized Design (CRD). The study was conducted with five fertilizer treatments, namely NPK, White KNO₃, Magnesium, Humic Acid, and Compost, and four applications for each treatment, resulting in a total of 20 experimental units. The planting medium used was soil with a neutral pH, according to the optimal conditions for grape growth. The parameters observed were the length of the grape seedlings measured using a measuring instrument. The results of the analysis of variance (ANOVA) showed that fertilizer administration had a significant effect on the length of the grape seedlings. Duncan's further test divided the treatments into three groups, with NPK fertilizer giving the best results, achieving an average seedling length of 164.25 cm, followed by White KNO₃, Humic Acid, and Magnesium with similar results but not significantly different. Compost fertilizer produced the lowest seedling length of 93.75 cm. Based on these findings, NPK fertilizer is recommended to increase the growth of grape seedlings optimally.